Penatalaksanaan Proses Fisioterapi pada Kasus Pressure Ulcer e.c Morbus Hansen di RSUD Sumber Glagah Mojokerto : A Case Report - Ardhita Hilwa Zakia; Isnaini Herawati; Ayu Dwi Lestari (Jurnal Medika Nusantara, 2025)
Background: Leprosy is a contagious skin disease caused by Mycobacterium Leprae. Leprosy is divided into 2, namely pausi bacillary (PB) dry type leprosy with a small number of lesions and multi bacillary (MB) wet type leprosy which is more severe. Purpose: this study aims to provide intervention in cases of pressure ulcer ec morbus hansen and to determine the results related to development after intervention. Method: provide treatment in the form of stretching, active assisted exercise, ankle pumping exercise, and crutch training. Stretching is given 1x a day with an intensity according to the patient's condition, 2 sets of each movement per AGA and AGB region. Active assisted exercise is done 2x a day with an intensity according to the patient's condition, 2 sets of each movement per AGA and AGB region. Ankle pumping exercise is done 2x a day with intensity according to patient condition, 2 sets of each leg movement. Conclusion: the results obtained are an increase in the range of motion, an increase in muscle strength, a decrease in swelling and in the evaluation results of functional activities using the Barthel index in ankle.